In vitro gas techniques and efficiency of microbial substrate degradation - Blümmel, Michael; Fernández Rivera, S. (2002)
In vitro techniques used for evaluating ruminant feeds can be classified into those that estimate gravimetrically their digestibility or degradability by quantifying the insoluble residues that remain after their incubation in inoculum containing rumen fluid, and those that measure the appearance of fermentation products such as gases. This paper reviews the development of three important in vitro techniques and addresses some problems associated with them. It is argued that whereas in vitro gas techniques have received much attention over the last two decades on account of the ease with which gas production kinetics can be assessed, there is little hard evidence of their superiority over gravimetric techniques. A conceptual problem with in vitro gas measurements arises from the variation in the proportion of products of microbial degradation of feeds, i.e. short chain fatty acids (SCFA), microbial biomass and gases. It is demonstrated that a close stoichiometrical relationship exists between SCFA and gas production, and that both products can practically be considered as one fermentative complex. A potentially competitive relationship exists between this complex and microbial growth with respect to substrate utilization. This problem can be overcome by measuring true substrate degradability concomitantly with gas production. On this account, this paper advances the hypothesis that it is possible to select feeds with high degradability in the rumen and less gas released in relation to the amount of substrate degraded, which has direct implications as a means for improving the efficiency of utilization of feeds for meat and milk production, while decreasing the emissions of gases to the atmosphere.